2009
DOI: 10.1094/cchem-86-2-0139
|View full text |Cite
|
Sign up to set email alerts
|

Influence of High Molecular Weight Glutenins on Viscoelastic Properties of Intact Wheat Kernel and Relation to Functional Properties of Wheat Dough

Abstract: High and low molecular weight glutenin subunits (HMW‐GS and LMW‐GS, respectively) are the main factors determining the viscoelastic properties of wheat dough. The mechanical and viscoelastic properties of 29 samples of wheat kernels differing in HMW‐GS were evaluated with load‐compression tests. Samples were grouped by genotypes differing in HMW‐GS composition (allelic variants: Glu‐A1: null, 1, 2*; Glu‐B1: 7, 7+8, 7+9, 13+16, and 17+18; Glu‐D1: 5+10, 2+12). Groups representing Glu‐A1 1 and 2*; Glu‐B1 7, 7+9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 26 publications
4
16
0
1
Order By: Relevance
“…The general tendency of the relationship between Glu-D1 HMW-GS composition, and dough rheological and breadmaking quality, as reported by several authors (Branlard and Dardevet, 1985;Figueroa et al, 2009Figueroa et al, , 2011bLuo et al, 2001;Payne et al, 1987;Tohver, 2007) was consistent with our data.…”
Section: Glu-a1supporting
confidence: 93%
See 2 more Smart Citations
“…The general tendency of the relationship between Glu-D1 HMW-GS composition, and dough rheological and breadmaking quality, as reported by several authors (Branlard and Dardevet, 1985;Figueroa et al, 2009Figueroa et al, , 2011bLuo et al, 2001;Payne et al, 1987;Tohver, 2007) was consistent with our data.…”
Section: Glu-a1supporting
confidence: 93%
“…This value is in the same range reported by other authors for stress relaxation tests on intact wheat kernels (Ponce-García et al, 2008;Figueroa et al, 2009). The retarded modulus of elasticity (E 1 and E 2 ) increased their values by about 5 Â 10 3 MPa.…”
Section: Comparison Of Creep and Compliance Parameters Of Glu-1 Andsupporting
confidence: 89%
See 1 more Smart Citation
“…Among Glu-B1 and Glu-D1 alleles, Glu-B1i and Glu-D1d showed strongest effects and negated the influence of alleles encoded at Glu-3 loci. Glu-A1b showed stronger effect on sedimentation volume and mixograph parameters as compared to Glu-A1a and c. Luo et al (2001) also reported stronger relationship of Glu-A1b allele, however, He et al (2005), Liu et al (2005), Figueroa et al (2009) and Tabiki et al (2006) suggested the stronger role of Glu-A1a in quality parameters. Surprisingly, there was no significant effect of Glu-B1 and Glu-D1 loci on mixograph mixing time, but variation at Glu-A1 significantly influenced mixing time.…”
Section: Effect Of Hmw and Lmw Glutenins On Sedimentation Volume And mentioning
confidence: 81%
“…Wheat (Triticum spp. The primary limitation of these methods relates to the complex geometry of the wheat kernel itself (Shpolyanskaya 1952;Kozma and Cunningham 1962;Shelef and Mohsenin 1967;Arnold and Roberts 1969;Multon et al 1981;Al Saleh and Gallant 1985;Glenn and Johnston 1992;Dobraszczyk 1994;Kang et al 1995;Ponce-García et al 2008;Elbatawi 2009;Figueroa et al 2009). durum) (Morris 2002;Bhave and Morris 2008).…”
mentioning
confidence: 99%